COMPARATIVE STUDY OF THE EFFECT OF RICE HUSK ASH AND WASTE GLASS ON COMPRESSIVE STRENGTH AND WATER ABSORPTION RATIO OF CONCRETE COMPOSITES (2014)
The problem of disposing and managing solid waste in nigeria where there is no visible regulation has become one of the major threats. with the recent ban on importation of rice by federal Government of Nigeria in order to boost local rice production, as well as the increase in volume of glass waste due to its use year-in-year-out in shops, construction sites and factories, wastes arising from these materials are expected to be on the increase. In order not to add to the environmental problems already being experienced in Nigeria, alternative and environmentally friendly uses must be found for these wastes. This study was conducted to determine and compare the compressive strength of concrete using rice husk burnt into ashes (RHA) and ground glass as replacement for fine aggregates at varying proportions for possible use in rural structures. Concrete mixture of 1:3:5 ratio (i.e. cement-sand-granite) was adopted for the study. While the proportion of cement and granite was kept constant, sand was gradually replaced with RHA and crushed glass in separate mixtures. Five replicates of each composite mixture were produced and tested in line with ASTM standard C67-07a after 28 days of water curing. Findings reveal that composites having about 66.7% to 100% of glass replacement gave better compressive strength than the control specimens with values ranging from 10.6N/mm2 to 12.2N/mm2 compared with a mean value of 9.6N/mm2 obtained from testing the control specimens. However, composites having about 16.7% of RHA replacement had compressive strength greater than the control with 11.9N/mm2. At total substitution of sand with RHA and glass wastes, water absorption ratiowas 47.5% and 10.9% respectively in RHA-concrete and glass-concrete composites compared with the control which was 9.1%. It was concluded that using both RHA and glass in concrete composite mixtures may be a viable option for rural structures in Nigeria and Africa at large in the nearest future while further work was recommended on the testing of other properties as well as the use of other solid waste materials and agricultural residues.